Comparative Analysis of Higher Education Financing Policies Used by OECD Member Countries and Financing Policy Proposal for Türkiye - Çetinkaya, Reşit; Çavdar, Ertuğrul (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2024)
The Turkish higher education system has developed remarkably in parallel with the developments and changes in the world today. With the ease of access to higher education for students and the increase in the number of students, higher education costs are increasing. This situation puts the higher education system under financial pressure in countries that provide higher education financing from public sources. In this study, higher education financing methods used worldwide are compared and the most appropriate financing method for Türkiye is discussed. For this purpose, the Entropy method was used in weighting the criteria determined for the evaluation of financing policies, and the performance analysis of the alternatives was carried out with the TOPSIS method, which is one of the multi-criteria decision-making methods. Alternative decision options for financing higher education are based on "No Fee", "Pre-charging" and "Income-Contingent Loan-ICL" methods and the main criteria are enrollment, education expenditures and labor force. In this context, sub-criteria were created and the financing methods used by OECD countries were analyzed. Within the scope of the study, it has been determined that the financing methods used by Norway, the Netherlands and the United Kingdom in higher education systems are in the top three. In this context, it has been determined that the "Income-Contingent Loan" method used by the first and third ranked countries is the most preferred method in terms of performance.
Keywords: Higher education; financing; TOPSIS; ICL; Other Fields of Education (Other); Yükseköğretim; Finans; TOPSIS; Alan Eğitimleri (Diğer); 4. Education; 1. No poverty